JOB DEMANDS – JOB RESOURCE: SYSTEMATIC LYTERATURE REVIEW - Aris Prilatama; Cindy Pramita; Sopiah (Transpublika Publisher, 2023)
This systematic literature review aims to summarize various studies on the relationship between job demands and job resources. This research utilized the SLR (Systematic Literature Review) method. Journals were obtained from Publish or Perish by selecting Scopus sources. The keywords used were